Vessel sound causes hearing loss for hummingbird bobtail squid (Euprymna berryi) - Putland, Rosalyn L.; Mooney, T. Aran; Mensinger, Allen F. (Frontiers in Marine Science, 2023)
Anthropogenic activity and its associated sounds have been shown to incur adverse effects on the behaviour and physiology of a wide range of aquatic taxa, from marine mammals to fishes. Yet, little is known about how invertebrates detect and respond to anthropogenic sound. The hummingbird bobtail squid (Euprymna berryi) has a short lifespan (< 6 months), grows to sexual maturity around 90 days post hatching and its small size (< 5 cm mantle length) makes the species an ideal candidate to examine potential effects of sound exposure under laboratory conditions. Hearing and behavioural observations were made before, during and after 15 minutes of vessel sound playback, and aural sensitivity curves were determined using auditory evoked potentials. A significant decrease in relative ventilation rate was observed during and post sound exposure. Auditory sensitivity before and after vessel sound exposure was also examined for three different ages: juveniles, mid- and late adults. Baseline audiograms indicated that there was a decrease in aural sensitivity with age. All three age groups showed similar, significantly decreased hearing sensitivity following sound exposure, however auditory sensitivity recovered within two hours. Globally, anthropogenic sounds have become louder and more persistent, therefore there may be limited time for these animals to recover from sound exposure. Given their ecological and economic importance, cephalopods should be considered in management and policy on underwater noise owing to potential adverse effects of anthropogenic sound on behaviour and physiology.